2021
DOI: 10.1126/sciadv.abf0364
|View full text |Cite
|
Sign up to set email alerts
|

Cues conditioned to withdrawal and negative reinforcement: Neglected but key motivational elements driving opioid addiction

Abstract: Opioid use disorder (OUD) is a debilitating disorder that affects millions of people. Neutral cues can acquire motivational properties when paired with the positive emotional effects of drug intoxication to stimulate relapse. However, much less research has been devoted to cues that become conditioned to the aversive effects of opioid withdrawal. We argue that environmental stimuli promote motivation for opioids when cues are paired with withdrawal (conditioned withdrawal) and generate opioid consumption to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 171 publications
(213 reference statements)
1
19
0
Order By: Relevance
“…The increased intracranial self-stimulation (ICSS) thresholds observed during sequential daily extended-access self-administration sessions in this study were consistent with prior results showing brain reward changes following extended access to self-administration of several different drugs (Ahmed et al, 2002;Jang et al, 2013;; this similarity is emphasized in the eight consecutive day experiment (Figure 4a). This pattern has been interpreted as key support for the negative reinforcement hypothesis in those reports (also see Pantazis et al, 2021;Zernig et al, 2007). The interpretation that dependence-related negative affect drove the escalated oxycodone IVSA in this study is further supported by the finding that when ICSS thresholds were elevated, the self-administration of oxycodone (or heroin) for 1 h (Figure 5), or non-contingent injection of an appropriate dose of oxycodone (Figure S2), was able to normalize thresholds towards baseline.…”
Section: Discussionsupporting
confidence: 78%
“…The increased intracranial self-stimulation (ICSS) thresholds observed during sequential daily extended-access self-administration sessions in this study were consistent with prior results showing brain reward changes following extended access to self-administration of several different drugs (Ahmed et al, 2002;Jang et al, 2013;; this similarity is emphasized in the eight consecutive day experiment (Figure 4a). This pattern has been interpreted as key support for the negative reinforcement hypothesis in those reports (also see Pantazis et al, 2021;Zernig et al, 2007). The interpretation that dependence-related negative affect drove the escalated oxycodone IVSA in this study is further supported by the finding that when ICSS thresholds were elevated, the self-administration of oxycodone (or heroin) for 1 h (Figure 5), or non-contingent injection of an appropriate dose of oxycodone (Figure S2), was able to normalize thresholds towards baseline.…”
Section: Discussionsupporting
confidence: 78%
“…Also distinct from food craving, which can be positively motivating [83], opioid craving is typically experienced as a negative affective state [36][37][38][39][40][41]. To determine the influence of concomitant negative mood, we continuously assessed participants' current stress, happiness, and boredom.…”
Section: Discussionmentioning
confidence: 99%
“…Craving for drugs, particularly opioids, co-occurs with a mixture of (mostly negative) affective experiences [36][37][38], sometimes referred to as 'hyperkatifeia' [39][40][41]. However, negative mood has incidental effects in decision-making [42][43][44], and could be expected to shift value globally rather than specifically for the drug, increasing the attractiveness of both drug-and nondrugrelated options.…”
Section: Introductionmentioning
confidence: 99%
“…Although sex differences in opioid dependence have been reported in humans and rodents ( Zachry et al, 2019 ; Marchette et al, 2021 ; Pantazis et al, 2021 ), most studies were conducted in male subjects. Previous studies found that female opioid-dependent mice and rats exhibited similar levels of somatic signs of naloxone-precipitated heroin withdrawal compared with male opioid-dependent mice and rats ( Cicero et al, 2002 ; Towers et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%